Cycloaddition of CO2 with epoxides and esterification reactions using the porous redox catalyst Co-POM@MIL-101(Cr). (18th September 2019) - Marandi, Afsaneh; Bahadori, Mehrnaz; Tangestaninejad, Shahram; Moghadam, Majid; Mirkhani, Valiollah; Mohammadpoor-Baltork, Iraj; Frohnhoven, Robert; Mathur, Sanjay; Sandleben, Aaron; Klein, Axel
Abstract : The catalytic activity of the Co-POM@MIL-101(Cr) composite in solvent-free cycloaddition of CO2 to epoxides and esterification of acetic acid with alcohols is due to an outer-sphere electron transfer mechanism using the Co(iii )/Co(ii ) redox pair. Abstract : The catalytic activity of the recently reported Co-POM@MIL-101(Cr) composite, synthesized from K5 [CoW12 O40 ] (Co-POM) and chromium(iii ) terephthalate (MIL-101), was studied in the solvent-free cycloaddition of CO2 with epoxides and esterification of acetic acid with various alcohols. The materials containing varying amounts of Co-POM were synthesized using a one-pot HF-free method in a "bottle around ship" strategy. The material was thoroughly characterized using several methods such as powder X-ray diffraction (PXRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), and electron paramagnetic resonance spectroscopy (EPR). Temperature programmed desorption (TPD) of NH3 and CO2, and the CO2 adsorption capacity (adsorption isotherms) were used to study the acid–base properties of the materials. The combination of the electron-transfer character of Co(iii )-POM and ordered mesopores in MIL-101(Cr) creates an efficient catalytic system with mild conditions (90 °C and 20 bar CO2 pressure) for solvent-free cycloaddition of CO2 to various epoxides. Esterification of acetic acid with alcohols was also carried out using the Co-POM@MIL-101 catalysts and high yields were achieved for different alcohols. The catalysis experiments also clearly show that the active site in this heterogeneous catalyst is the Co(iii ) center in the Keggin anion structure. It presumably conducts both the cycloaddition of CO2 to epoxides and the esterification reaction via an outer-sphere electron transfer mechanism using the Co(iii )/Co(ii ) redox pair. The heterogeneous Co-POM@MIL-101 catalysts were separated by simple filtration and reused five times in the cycloaddition of CO2 with styrene epoxide and seven times for the esterification of acetic acid with benzyl alcohol with negligible leaching of Co-POM and no considerable loss of activity.